2010
DOI: 10.1002/pon.1890
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based cognitive therapy reduces chronic cancer‐related fatigue: a treatment study

Abstract: Mindfulness-based cognitive therapy is an effective treatment for chronic cancer-related fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 58 publications
3
123
0
6
Order By: Relevance
“…Rimes and Windgrove conducted a mindfulness based cognitive therapy (MCBT) pilot study (n = 35) for patients with chronic fatigue syndrome who are still suffering from fatigue after CBT. They gained promising results showing significant improvements in fatigue and depressed mood [94] Other studies have found MCBT useful in chronic cancer related fatigue also [95].…”
Section: Treatmentmentioning
confidence: 99%
“…Rimes and Windgrove conducted a mindfulness based cognitive therapy (MCBT) pilot study (n = 35) for patients with chronic fatigue syndrome who are still suffering from fatigue after CBT. They gained promising results showing significant improvements in fatigue and depressed mood [94] Other studies have found MCBT useful in chronic cancer related fatigue also [95].…”
Section: Treatmentmentioning
confidence: 99%
“…Since advances in the treatment of cancer as well as chronic illnesses have afforded patients longer survival, there has been renewed interest in managing persistent, complex, and distressing symptoms that affect health-related quality of life (QoL) and productivity. One of the most common and debilitating side effects of RT is fatigue [1, 2]. Cancer-related fatigue can persist for months to years after treatment completion, with about 25–33% of cancer patients reporting persistent fatigue [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common and debilitating side effects of RT is fatigue [1, 2]. Cancer-related fatigue can persist for months to years after treatment completion, with about 25–33% of cancer patients reporting persistent fatigue [1, 3]. Fatigue can negatively impact all aspects of health-related QoL, including functional ability and the performance of activities of daily living [2-4].…”
Section: Introductionmentioning
confidence: 99%
“…En los artículos seleccionados se halló el mindfulness con aplicación a la patología oncológica [7,51,52,53,54,55,56,57,58,59,60,61,62,63], así como su uso en otras patologías crónicas [4,18,64,65]. Se ha demostrado su efecto fisiológico en la reducción de marcadores de ansiedad, como la respuesta humana al cortisol [66,67].…”
Section: Mindfulness (178 %)unclassified